Orchids of the Southern Cone (1830-2000) - Part III : Karl Friedrich Reiche's Orchidaceae Chilensis and a commentary about Friedrich Wilhelm Ludwig Kraenzlin's Orchidacearum Genera et Species (Vol. 2, Part I) - Ossenbach Sauter, Carlos 1947-
Karl Reiche (1860-1929), a German botanist, arrived in Chile in 1889 as a professor at the Lyceum in the city of Constitución. He was attracted by the country's climate and its traditional friendliness to German immigrants. A few years later, in 1897, Federico Phillippi, Director of the Museo Nacional de Historia Natural, welcomed Reiche as the new Head of the Botanical Section, a position he held until 1910. During his 21 years in Chile, Reiche worked intensively on the Chilean flora and was a prolific writer. Besides six volumes of the Estudios críticos de la Flora de Chile (1896-1911), several editions of Reiche's Plant Geography of Chile were published (1907, 1934-1937, 2013), a magnificent essay on Chiles' Orchidaceae, Orchidaceae Chilensis (1910, reprint 2007), and several other minor works. On Reiche's suggestion, The Museo Nacional engaged Friedrich Kraenzlin (1847-1934) to write a treatment of the orchids of the Southern Cone. It was published in 1904 as the second volume of Orchidacearum Genera et Species. Thiswork was widely criticized by many botanists, including Reiche himself.